(3GdSdhc GdaYGd aj GdefXeGJ (B/s - (3YHO GdHGbj, UdGM GdOjf eMeOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2004)
(3GdeONd Gdi GdSdhc GdJfXjej(B- (3GdeDKQGJ GdaQOjI aj GdSdhc GdEfSGfj(B- (3GdeDKQGJ GdLeGYjI aj GdSdhc GdEfSGfj(B- (3GdeDKQGJ GdJfXjejI aj GdSdhc GdJfXjej(B- (3GdJWHjbGJ hGdJOQjHGJ GdYedjI(B.s
Keywords: (3GdSdhc GdaYGds; (3GdefXeGJs